2021
DOI: 10.1108/jfra-04-2021-0103
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing earnings management preferences from business strategies

Abstract: Purpose This study aims to examine the preference for earnings management (EM) strategies according to business strategies, namely, cost leadership strategies and differentiation strategies, Design/methodology/approach This study analyzed 262 samples of manufacturing and service companies listed on the Indonesia Stock Exchange for the period 2019. Logistic regression analysis is used to test the company’s EM strategy preferences based on the applied business strategy. Findings The results prove that business… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…Research identifies improvements needed in accrual models, highlighting their occasional distortion of economic realities, sensitivity to accounting choices and omission of cash flow data. These models also suffer from limited generalizability due to assumptions not reflecting real-world conditions and vulnerability to changes in variable selection or model specification, questioning their robustness (McNichols and Stubben, 2018; Ogbaisi and Aronmwan, 2022; Dbouk and Zaarour, 2017; Purba et al , 2022; Dechow and Dichev, 2002; Dechow et al , 2012; Peasnell et al , 2000). Despite these critiques, integrating ML presents opportunities to improve financial models’ accuracy and relevance, emphasizing the need for ongoing innovation and critical evaluation in financial analytics.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Research identifies improvements needed in accrual models, highlighting their occasional distortion of economic realities, sensitivity to accounting choices and omission of cash flow data. These models also suffer from limited generalizability due to assumptions not reflecting real-world conditions and vulnerability to changes in variable selection or model specification, questioning their robustness (McNichols and Stubben, 2018; Ogbaisi and Aronmwan, 2022; Dbouk and Zaarour, 2017; Purba et al , 2022; Dechow and Dichev, 2002; Dechow et al , 2012; Peasnell et al , 2000). Despite these critiques, integrating ML presents opportunities to improve financial models’ accuracy and relevance, emphasizing the need for ongoing innovation and critical evaluation in financial analytics.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…In contrast, market competition negatively moderated the prospectors' strategy influence on REM. Purba et al (2022) investigated the preference for earnings management based on business strategies, cost leadership strategies (defenders), and differentiation strategies (prospectors). They analyzed 262 samples of non-financial firms listed on the Indonesian Stock Exchange in 2019.…”
Section: Business Strategy and Real Earnings Managementmentioning
confidence: 99%
“…According to the aforementioned preceding literature, it can be concluded that -Previous studies have rarely examined the influence of a firm's business strategy on engaging in REM in general. Recently, limited studies reviewed the impact of opposing sides of the strategy chain, prospector's and defender's business strategies, on REM (Robiansyah et al, 2020;Purba et al, 2022;Herusetya et al, 2023). However, no studies have investigated such a relationship in Egypt or Middle Eastern countries.…”
Section: ‫ال‬ ‫مجلة‬ ‫المحاسبية‬ ‫بحوث‬ ‫ال‬ ‫العدد‬ ‫يونيو‬ ‫ثانى‬ 2023mentioning
confidence: 99%
See 1 more Smart Citation
“…27-48). Logistic regression was performed as described by Purba et al (2021). The least-squares method was used by Ismael and Kamel (2021), Bhutta et al (2021), andChakroun et al (2022, pp.…”
Section: Literature Reviewmentioning
confidence: 99%